The Impact of Financing Risk on Islamic Banking Performance in Indonesia - Iwan Setiawan (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
The financing risk is a significant issue in the Islamic banking industry that affects its performance. This research aims to examine the factors that influence financing risk on the financial performance of Islamic banking in Indonesia. This study utilized time-series data quarterly from 2009-2020 collected from three types of Islamic banking in Indonesia: Islamic Commercial Bank (ICB), Islamic Business Unit (IBU), and Islamic Rural Bank (IRB). It was analyzed using multiple regression estimation techniques with the Ordinary Least Square (OLS) method. This study revealed that the Islamic banks’ financing risk is significantly influenced by bank capital, financing, economic growth, inflation, and central bank’ rate (BI rates), both negatively and positively. In detail, the increase of bank capital, financing, and economic growth will reduce the financing risks, whilst inflation and BI rate increase the financing risks. The findings also disclosed that Islamic banks' financial performance is influenced by bank capital, operating costs, financing risks, inflation, and BI rates. Thus, the decrease in bank capital, operational costs, and financing risks will subsequently decrease the financial performance, while the increase of inflation and BI rates will increase the financial performance of Islamic banks. Economic growth is the most influential factor in reducing financing risk, while financing risk is the most significant factor in improving banks’ financial performance. The government's efforts to boost economic growth are crucial to reducing financing risks and improving the financial performance of Islamic banks.==========================================================================================================ABSTRAK – Dampak Risiko Pembiayaan terhadap Kinerja Bank Syariah di Indonesia. Risiko pembiayaan merupakan persoalan utama bagi industri perbankan termasuk perbankan syariah. Tujuan dari penelitian ini adalah untuk menganalisis faktor-faktor yang mempengaruhi risiko pembiayaan dan pengaruhnya terhadap kinerja keuangan perbankan syariah di Indonesia. Objek penelitian meliputi Bank Umum Syariah, Unit Usaha Syariah dan Bank Perkreditan Rakyat syariah. Model analisis menggunakan teknik estimasi regresi berganda dengan menggunakan metode  Ordinary Least Square (OLS). Penelitian ini menggunakan data time-series periode kuartalan dari 2009-2020. Hasil penelitian ini menunjukkan bahwa risiko pembiayaan bank syariah dipengaruhi oleh modal bank, pembiayaan, pertumbuhan ekonomi, inflasi dan BI Rate. Hasil ini mengindikasikan bahwa peningkatan modal bank, pembiayaan, dan pertumbuhan ekonomi akan mengakibatkan penurunan risiko pembiayaan, sementara peningkatan inflasi dan BI Rate akan meningkatkan risiko pembiayaan. Selain itu, hasil kajian juga mendapati bahwa kinerja keuangan bank syariah dipengaruhi oleh modal bank, biaya operasional bank, risiko pembiayaan, inflasi dan BI Rate. Secara detil, penurunan modal bank, biaya operasional dan risiko pembiayaan akan meningkatkan kinerja keuangan bank syariah, sementara peningkatan inflasi dan BI Rate akan meningkatkan kinerja keuangan. Faktor yang berpengaruh paling terhadap penurunan risiko pembiayaan adalah pertumbuhan ekonomi. Penurunan risiko pembiayaan merupakan faktor yang berpengaruh paling besar terhadap peningkatan kinerja keuangan perbankan syariah. Upaya pemerintah untuk mendorong pertumbuhan ekonomi merupakan langkah yang sangat strategis mengurangi risiko pembiayaan dan meningkatkan kinerja keuangan perbankan syariah di Indonesia.